Penerapan Model PBL (Problem Based Learning) untuk Meningkatkan Hasil Belajar IPA Kelas V di SDN 48 Cakranegara - Islamiati, Dian; Asti, Rukmana; Amrullah, Amrullah (Lembaga Yasin AlSys, 2023)
The background of this research is the science learning outcomes of fifth grade students at SDN 48 Cakranegara. After looking at these problems, one solution to overcome this problem is to use the Problem Based Learning (PBL) learning model. The purpose of this study was to determine the application of the Problem Based Learning (PBL) learning model to improve students' natural science learning outcomes at SDN 48 Cakranegara. This research method is Classroom Action Research (PTK) which is carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementing, observing, reflecting, and when the research is carried out. The research subjects in this study were 27 class V students. Data collection techniques in the form of documentation, observation, and learning achievement tests. The results of this study indicate that the results of science learning in class V SDN 48 Cakranegara. The results of this study indicate that the results of learning science in class V SDN 48 Cakranegara in cycle I, based on the calculations that have been done, it is known that students who have fulfilled the KKM, namely ≥ 75, have 18 students (67%). This can be seen from the number of students who get a score of 75 and above. While students who have not reached KKM ≤ 75, namely there are 9 students (33%). Furthermore, in cycle II, the average value of students who have fulfilled the KKM is ≥ 75, there are 23 students (85%). This can be seen from the number of students who get a score of 75 and above. Meanwhile, there were 4 students (15%) who had not reached KKM ≤ 75. Where this percentage can be said that it has reached the criteria for student learning success, where students get a value of ≥ 75. Thus it can be concluded that using the Problem Based Learning learning model can improve student learning outcomes in class V SDN 48 Cakranegara.